2014
DOI: 10.1021/es5032344
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Drinking Water Disinfection Byproducts: Cell Cycle Alterations Induced by the Monohaloacetonitriles

Abstract: Haloacetonitriles (HANs) are a chemical class of drinking water disinfection byproducts (DBPs) that form from reactions between disinfectants and nitrogen-containing precursors, the latter more prevalent in water sources impacted by algae bloom and municipal wastewater effluent discharge. HANs, previously demonstrated to be genotoxic, were investigated for their effects on the mammalian cell cycle. Treating Chinese hamster ovary (CHO) cells with monoHANs followed by the release from the chemical treatment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 68 publications
0
46
0
Order By: Relevance
“…Therefore, disinfection should be taken with great care, especially when using source waters with elevated Br À and I À levels. Increasing evidence shows that brominated and iodinated DBPs are more toxic than their chlorinated analogues (Plewa and Wagner, 2009;Plewa et al, 2004;Richrdson et al, 2007;Komaki et al, 2014). According to a comprehensive genotoxicity/cytotoxicity database of the DNA damage and cytotoxicity study with CHO cell assays, halogenated DBPs follow a toxicity order of I À > Br À > Cl À as shown in Fig.…”
Section: Toxicity Of Desalinated Watersmentioning
confidence: 99%
“…Therefore, disinfection should be taken with great care, especially when using source waters with elevated Br À and I À levels. Increasing evidence shows that brominated and iodinated DBPs are more toxic than their chlorinated analogues (Plewa and Wagner, 2009;Plewa et al, 2004;Richrdson et al, 2007;Komaki et al, 2014). According to a comprehensive genotoxicity/cytotoxicity database of the DNA damage and cytotoxicity study with CHO cell assays, halogenated DBPs follow a toxicity order of I À > Br À > Cl À as shown in Fig.…”
Section: Toxicity Of Desalinated Watersmentioning
confidence: 99%
“…Inhibition of GAPDH leads to pyruvate starvation and mitochondrial stress that generates ROS (58,59). New research demonstrated that the monohalonitriles, at non-cytotoxic concentrations, impact the M-phase of the cell cycle and induce hyperploidy in mammalian cells (35). These examples indicate that the molecular mechanisms of DBP toxicity involve a diversity of cellular targets and affect a host of different biological pathways.…”
Section: Molecular Mechanisms Of Action Of the Dbp Forcing Agents Assmentioning
confidence: 99%
“…Research into the formation, occurrence, toxicity, epidemiology and engineering processes have resulted in enhanced interest in the adverse impact of DBPs on the environment and the public health (12,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Although the last decade experienced increased interdisciplinary collaborations amongst chemists, biologists, epidemiologists and engineers, resolving the risks of DBPs follows a dated paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Drinking water disinfection effectively reduces waterborne diseases (Akin et al 1982) but the formation of disinfection by-products (DBPs) has raised concerns due to their potential adverse health effects (Cantor et al 2010, Komaki et al 2014, Plewa et al 2008b. Some of the 600 to 700 known DBPs have been toxicologically characterized with in vitro bioassays and a few with chronic in vivo studies demonstrating that some DBPs are potent cytotoxicants, genotoxicants, and carcinogens (Plewa et al 2010, Plewa et al 2008b, Richardson et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Attack of proteins by soft electrophilic DBPs, for example, can lead to enzyme inhibition and depletion of glutathione, which causes a multitude of subsequent effects, such as generation of reactive oxygen species (ROS), impaired DNA repair, or disturbed DNA replication. This can indirectly result in genotoxic effects (Komaki et al 2014, Komaki et al 2009.…”
Section: Introductionmentioning
confidence: 99%